1967
DOI: 10.1111/j.1151-2916.1967.tb15046.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in the System BaTiO3-KnbO3

Abstract: Solid solution formation in the systemBaTiOr gabor was established by X-ray diffraction and dielectric measurements. Solid solutions with cubic symmetry were observed in the composition range from 4 to 90 mole yo I u y b o a at room temperature. The lattice parameter for the BaTiOp solid solutions increased with increasing -boa;that for the KNbOa solid solutions decreased with the addition of BaTiOa. A distinct discontinuity in lattice parameter was observed at the composition containing about 65 mole yo BaTiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 4 publications
4
39
2
Order By: Relevance
“…Given the existence of hysteresis in a first order phase transition, the transition temperature is expressed in the phase diagram as the average of the transformation temperatures, i.e., the peak temperatures of the transformation, during a heating and a cooling trend. The transition temperatures of the ''as-prepared'' samples in the present study have been compared with the published data of the KNbO 3 -BaTiO 3 phase diagram by Bratton [6], as shown in Fig. 3.…”
Section: Dscmentioning
confidence: 98%
See 2 more Smart Citations
“…Given the existence of hysteresis in a first order phase transition, the transition temperature is expressed in the phase diagram as the average of the transformation temperatures, i.e., the peak temperatures of the transformation, during a heating and a cooling trend. The transition temperatures of the ''as-prepared'' samples in the present study have been compared with the published data of the KNbO 3 -BaTiO 3 phase diagram by Bratton [6], as shown in Fig. 3.…”
Section: Dscmentioning
confidence: 98%
“…3. In that study, the transition temperatures were obtained from maximums on the dielectric constant-temperature curves [6]. Figure 4 shows the temperature dependence of the dielectric constant of 3%KNbO 3 -BaTiO 3 at 10 kHz in both heating and cooling (0.01 8C/s).…”
Section: Dscmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the high piezoelectric properties have been reported for a BT/KN composite and they were explained to be attributed to the interfaces between tetragonal BT grains and orthorhombic KN grains [2]- [4],.The transmission electron microscopy (TEM) observation revealed that the interfaces were consisted of Ba-rich tetragonal grains and KN-rich orthorhombic grains [5]. Because both KN and BT grains remained for the composite, it is expected that the temperature dependence of the dielectric constant is a simple summation of the two, making it attractive high temperature dielectrics with high permittivity induced by the interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In increasing the volume of the unit cell, introducing BZ to NKN acts in a similar way as negative physical pressure, 15,16 and the increase of T OÀR could be understood. However, in the NKN-xBNZ solid solution, V p decreases, a behavior not in consistent with that under a negative physical pressure, T OÀR increases as well.…”
mentioning
confidence: 99%